2008
DOI: 10.1039/b610848m
|View full text |Cite
|
Sign up to set email alerts
|

Solvent resistant nanofiltration: separating on a molecular level

Abstract: Over the past decade, solvent resistant nanofiltration (SRNF) has gained a lot of attention, as it is a promising energy- and waste-efficient unit process to separate mixtures down to a molecular level. This critical review focuses on all aspects related to this new burgeoning technology, occasionally also including literature obtained on aqueous applications or related membrane processes, if of relevance to understand SRNF better. An overview of the different membrane materials and the methods to turn them in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
750
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,026 publications
(763 citation statements)
references
References 252 publications
(418 reference statements)
9
750
0
4
Order By: Relevance
“…Recently, we have demonstrated that nanopapers are a suitable candidate for the fabrication of organic solvent nanofiltration [23] membranes [22]. In addition to organic solvent nanofiltration membranes, such nanopapers are anticipated to serve as alternative for conventional polymer tight ultrafiltration membranes for water purification.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have demonstrated that nanopapers are a suitable candidate for the fabrication of organic solvent nanofiltration [23] membranes [22]. In addition to organic solvent nanofiltration membranes, such nanopapers are anticipated to serve as alternative for conventional polymer tight ultrafiltration membranes for water purification.…”
Section: Introductionmentioning
confidence: 99%
“…The role of additives in the gelation bath during the preparation of membranes by the wet phase inversion technique Brazilian Journal of Chemical Engineering has been reported. (Vandezande, 2008). The conformation of the membranes is varied by adding higher molecular weight alcohols (Boussu et al, 2006) (Deshmukh and Li, 1998) (Leblanc et al, 2001), the same solvents used for polymer solution (Bottino et al, 1985) (Konagaya, 2001), or macromolecular additives (Javiya et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This complex process limited the synthesis to volatile organic solvents, and the lengthy solvent switching system made the separation process unsuitable for large-scale 50 production. Molecular separation in organic solvents via nanofiltration (Organic Solvent Nanofiltration -OSN) is an emerging technology 11 , which should be an ideal separation method for in-cycle purification during peptide synthesis. The MEPS concept is illustrated in Figure 1.…”
mentioning
confidence: 99%